Pengaruh Keragaman Produk, Harga Dan Kualitas Pelayanan Terhadap Minat Beli Ulang Melalui Kepuasan Sebagai Variabel Intervening Pada Pelanggan MR.DIY Tlogomas Kota Malang - Abdul Haris; Rois Arifin; Muhammad Tody Arsyianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the direct and indirect influence between product diversity, price and service quality on repurchase interest through satisfaction as an intervening variable. This research is a type of explanatory research using a quantitative approach. The population in this study uses the malhotra formula with an unknown population and sampling in this study refers to the malhotra formula by multiplying the number of variables by the indicator known to the number of respondents as many as 105 respondents, with sampling using purposing sampling. In data collection using questionnaire instruments. Based on the results of the study, it is known that product diversity, price and service quality directly have a significant effect on repurchase interest. Product diversity, price and service quality directly have a significant effect on satisfaction. Product diversity, and service quality indirectly affect repurchase interest through satisfaction. And price has no effect on repurchase interest through satisfaction. Keywords: Product Diversity, Price and Service Quality, Satisfaction and            Repurchase Interest.